2023
DOI: 10.1186/s12967-023-03950-w
|View full text |Cite
|
Sign up to set email alerts
|

An initial study on the predictive value using multiple MRI characteristics for Ki-67 labeling index in glioma

Abstract: Background and purpose Ki-67 labeling index (LI) is an important indicator of tumor cell proliferation in glioma, which can only be obtained by postoperative biopsy at present. This study aimed to explore the correlation between Ki-67 LI and apparent diffusion coefficient (ADC) parameters and to predict the level of Ki-67 LI noninvasively before surgery by multiple MRI characteristics. Methods Preoperative MRI data of 166 patients with pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Ki-67 LI may be of value in the differential diagnostic setting, but it must not be over-interpreted in the clinicopathological context. In the innovative paper [16], the authors provide an initial study on the predictive value using multiple MRI characteristics for Ki-67 LI in glioma. Their results demonstrate that the degree of peritumoral edema was more severe in the group with high Ki-67 LI, which also suggested that there is a certain correlation between peritumoral edema and Ki-67 LI, both of which are related to the higher malignant degree of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Ki-67 LI may be of value in the differential diagnostic setting, but it must not be over-interpreted in the clinicopathological context. In the innovative paper [16], the authors provide an initial study on the predictive value using multiple MRI characteristics for Ki-67 LI in glioma. Their results demonstrate that the degree of peritumoral edema was more severe in the group with high Ki-67 LI, which also suggested that there is a certain correlation between peritumoral edema and Ki-67 LI, both of which are related to the higher malignant degree of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] The Ki-67 index is an important indicator of tumor cell proliferation in patients of glioma. [23] High Ki-67 index has been identified as a risk factor that can decrease OS and PFS in previous studies, and various cutoff points (range, 20%–30%) have been suggested. [24–27] In a study conducted by Caramanti et al, Ki-67 index was identified as an indicator of tumor aggressiveness, which correlated with the volume of peritumoral edema.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have successfully applied radiomics techniques to CT, MRI, and ultrasonography (US) for the diagnosis and prognostication of PNETs, highlighting their exceptional efficiency ( 31 33 ). Furthermore, previous studies have provided evidence to support a strong correlation between the radiomics features of the peritumoral region and various tumor-related factors, including diagnostic accuracy, pathological characteristics, and prognostic indicators ( 34 36 ).…”
Section: Introductionmentioning
confidence: 88%